2008
DOI: 10.1097/prs.0b013e31816aa0b3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes and Complications of Vascularized Toe Joint Transfer, Silicone Arthroplasty, and PyroCarbon Arthroplasty for Posttraumatic Joint Reconstruction of the Finger

Abstract: Vascularized toe joint transfer has a worse active arc of motion and a higher complication rate when compared with silicone implant arthroplasty for both proximal interphalangeal and metacarpophalangeal joints. Early data suggest that PyroCarbon implants may be associated with higher rates of major complications. Given the lack of improvement in outcomes for posttraumatic finger joint reconstruction over the past 40 years, research efforts should focus on future development of novel arthroplasty devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 29 publications
2
73
1
2
Order By: Relevance
“…The median active range of motion is mentioned between 30°and 47°f or the pyrocarbon prosthesis (ASCENSION TM ), 30-44°f or silicone prosthesis, 47°for AVANTA SBi, 29-60°for a ceramic prosthesis (Moje ® ) and 29-37°for vascularised toe joint transfer [2,24,25,27,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median active range of motion is mentioned between 30°and 47°f or the pyrocarbon prosthesis (ASCENSION TM ), 30-44°f or silicone prosthesis, 47°for AVANTA SBi, 29-60°for a ceramic prosthesis (Moje ® ) and 29-37°for vascularised toe joint transfer [2,24,25,27,30].…”
Section: Discussionmentioning
confidence: 99%
“…Common postoperative complications with PIP joint replacement mentioned in the literature are (1) tendon adhesions leading to loss of motion, (2) migration of the prosthesis/heterotopic bone formation/aseptic prosthesis loosening, (3) swan neck deformity and (4) infection of the implant bed [10,13,14,21,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed 21 studies and found a comparable active ROM in the PIP joint between the silicone and pyrocarbon implants (44 ± 11°and 43 ± 11°, respectively) [6].…”
Section: Discussionmentioning
confidence: 98%
“…Most of retrospective clinical studies found that pyrocarbon PIP joint arthroplasty provided patients with excellent pain relief overall and maintained their preoperative PIP joint motion; however, overall implant complications has been very variable, with some good outcomes at short-medium-term follow-up (Branam et al, 2007;Bravo et al, 2007;Chung et al, 2009;Desai et al, 2014;Mashhadi et al, 2012;McGuire et al, 2012;Watts et al, 2012) and some bad outcomes at medium-longer-term follow-up (Chan et al, 2013;Daecke et al, 2012;Dickson et al, 2015;Hutt et al, 2012;Ono et al, 2012;Reissner et al, 2014;Squitieri and Chung, 2008;Sweets and Stern, 2011). Implant loosening with migration, dislocation and implant fracture were the main reported clinical complications (Chan et al, 2013;Ceruso et al, 2017;Dickson et al, 2015;Sweets and Stern, 2011;Reissner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%